2016
DOI: 10.1105/tpc.16.00105
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis HOOKLESS1 regulates responses to pathogens and abscisic acid through interaction with MED18 and acetylation of WRKY33 and ABI5 chromatin

Abstract: Arabidopsis thaliana HOOKLESS1 (HLS1) encodes a putative histone acetyltransferase with known functions in seedling growth. Here, we show that HLS1 regulates plant responses to pathogens and abscisic acid (ABA) through histone acetylation at chromatin of target loci. The hls1 mutants show impaired responses to bacterial and fungal infection, accelerated senescence, and impaired responses to ABA. HLS1 modulates the expression of WRKY33 and ABA INSENSITIVE5 (ABI5), known regulators of pathogen and ABA responses,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
81
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(83 citation statements)
references
References 74 publications
2
81
0
Order By: Relevance
“…Genetic and biochemical studies have demonstrated that HLS1 is required for both ethylene‐ and light‐regulated ARF2 protein accumulation, but the underlying molecular mechanism is unclear (Li et al ., ). Consistent with the bioinformatic prediction that HLS1 shows sequence homology with N ‐acetyltransferases (Lehman et al ., ), a recent study has shown decreased levels of histone 3 acetylation at chromosome loci of WRKY33 and ABI5 ( ABA INSENSITIVE 5 ) in hls1 relative to that of the wild‐type (Liao et al ., ). However, direct evidence for the N ‐acetyltransferase activity of HLS1, either in vivo or in vitro , is missing (Liao et al ., ).…”
Section: Central Players Of Apical Hook Development: Auxin and Hookless1mentioning
confidence: 97%
See 1 more Smart Citation
“…Genetic and biochemical studies have demonstrated that HLS1 is required for both ethylene‐ and light‐regulated ARF2 protein accumulation, but the underlying molecular mechanism is unclear (Li et al ., ). Consistent with the bioinformatic prediction that HLS1 shows sequence homology with N ‐acetyltransferases (Lehman et al ., ), a recent study has shown decreased levels of histone 3 acetylation at chromosome loci of WRKY33 and ABI5 ( ABA INSENSITIVE 5 ) in hls1 relative to that of the wild‐type (Liao et al ., ). However, direct evidence for the N ‐acetyltransferase activity of HLS1, either in vivo or in vitro , is missing (Liao et al ., ).…”
Section: Central Players Of Apical Hook Development: Auxin and Hookless1mentioning
confidence: 97%
“…Consistent with the bioinformatic prediction that HLS1 shows sequence homology with N ‐acetyltransferases (Lehman et al ., ), a recent study has shown decreased levels of histone 3 acetylation at chromosome loci of WRKY33 and ABI5 ( ABA INSENSITIVE 5 ) in hls1 relative to that of the wild‐type (Liao et al ., ). However, direct evidence for the N ‐acetyltransferase activity of HLS1, either in vivo or in vitro , is missing (Liao et al ., ). In the light of apical hook development, whether and how this putative N ‐acetyltransferase activity, if it exists, impinges on auxin distribution and signaling remains to be explored (Li et al ., ).…”
Section: Central Players Of Apical Hook Development: Auxin and Hookless1mentioning
confidence: 97%
“…HLS1 and MED18 interact physically and probably are the part of the same complex. Using transgenic Arabidopsis plants it was proved that HLS1 and MED18 are engaged in ABA signaling and are tightly related to ABI5 action (Liao et al, 2016). …”
Section: Epigenetic Regulation Of the Abi5 Genementioning
confidence: 99%
“…This ABA-induced weakening of ROS production should be part of a larger defensive network where ABA acts as a moderating signal. Indeed, transcriptomic and epigenetic studies revealed that ABA down-regulates the expression of many defensive genes (de Torres-Zabala et al, 2007; Cheng et al, 2016; Liao et al, 2016). All these additive effects would explain the extremely susceptible phenotype of the ABA-overproducing plants, even more pronounced than the AtrbohD mutant’s one even if this mutant does not exhibit any oxidative stress response to infection ( Figures 5 , 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies highlighted the major involvement of ABA in the regulation network of plant defense. It induces the accumulation of HLS1, an histone acetyltransferase that regulates epigenetically defense responses (Liao et al, 2016), enhances expression of defense genes through the down-regulation of many miRNAs (Cheng et al, 2016) and its effects on cell wall composition and structure influence resistance to pathogens (Curvers et al, 2010; Sánchez-Vallet et al, 2012). All these data would explain the negative impact of ABA on pathogen defense in some pathosystems (Asselbergh et al, 2008b).…”
Section: Introductionmentioning
confidence: 99%